JAMALUDDIN AL-AFGHANI’S THOUGHTS IN SAREKAT ISLAM AND MUHAMMADIYAH MOVEMENT EARLY 20TH CENTURY - Mahardika, Moch. Dimas Galuh (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2023)
The global political struggle between Muslims and Western imperialists produced new Islamic thinkers. One of them was Jamaluddin Al-Afghani, a pioneer of pan-Islamism whose ideas spread to different parts of the world. His idea of ??political independence for Muslims became the compass for the figures of the early 20th-century movement in the Dutch East Indies, which carried out a movement against colonialism-imperialism. Some major organizations inspired by Jamaluddin Al-Afghani's thoughts are Sarekat Islam and Muhammadiyah. Both organisations play an important role in the machinery of the national movement. Written based on a literature study with a historical approach, the article attempts to explain the influence of Jamaluddin Al-Afghani's thoughts on the political dynamics of Islamic groups during the nationalist movement of the early 20th century.